Highly conductive ionogel electrolytes based on N-ethyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide FSI and NaFSI mixtures and their applications in sodium batteries. (21st June 2021) - Malunavar, Sneha; Wang, Xiaoen; Makhlooghiazad, Faezeh; Armand, Michel; Galceran, Montserrat; Howlett, Patrick C.; Forsyth, Maria
Abstract: The development of highly conductive and safe electrolytes for sodium-ion batteries is an emerging field beyond lithium battery technologies. In this work we have developed new ionogel electrolytes consisting of a binary mixture of an organic ionic plastic crystal, N -ethyl- N -methylpyrrolidiniumbis(fluorosulfonyl)imide (C2 mpyrFSI), mixed with NaFSI supported on a mat of electrospun poly (vinylidene fluoride) nanofibers. The salt mixture near the eutectic composition (35 mol% NaFSI) was selected for further study after a detailed phase diagram analysis and ionogel electrolytes based on this were prepared. The ionic conductivity of the prepared ionogel composite reaches 2.6 × 10 −3 S cm −1 at ambient temperature. This ionogel membrane possessed a relatively high Na-ion transference number of 0.44 at 50 °C and we demonstrate the performance of a Na metal full cell using a NaFePO4 cathode (1.75–4.0 V). The assembled cells show a good capacity retention with coulombic efficiency close to 100% at various C rates between C/20, C/10 and C/5, achieving 120 mAh g −1 at C/20. The long term charge/discharge performance is also demonstrated. Our study provides a feasible method to prepare highly conductive ionogel electrolytes for future Na-battery applications